2006
DOI: 10.1111/j.1445-2197.2006.03949.x
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Seroma Formation and Prevention in Breast Cancer Surgery

Abstract: Evidence suggests an increase in the incidence of seroma because of thermal trauma from electrocautery dissection, but this is indispensable for surgical haemostasis. Obliteration of dead space by various flap apposition techniques has been shown to be advantageous in reducing incidence and volume of seroma. Low-pressure suction drainage reduces seroma volume and duration of drainage leading to earlier drain removal. Preventive measures have to be tailored according to individual patient and operative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 90 publications
1
136
0
4
Order By: Relevance
“…6 The dead space created by dissected tissue is filled with serous fluid. 7 This fluid changes composition in the days following surgery.…”
Section: Pathogenesismentioning
confidence: 99%
“…6 The dead space created by dissected tissue is filled with serous fluid. 7 This fluid changes composition in the days following surgery.…”
Section: Pathogenesismentioning
confidence: 99%
“…2,15,16,34,43 Guidelines to safely increase shoulder motion have not been established, and their development is hampered by the lack of systematic methodology to design interventions. 16 Combining modeling studies and small clinical trials may lead to an optimal, cost-effective pipeline to design effectiveness studies.…”
Section: Supplemental Video Onlinementioning
confidence: 99%
“…33 Loss of flexibility of the muscle suggests the need to start stretching exercises as early as possible; however, exercise programs that start in the first days after surgery have been associated with an increased risk of seroma formation. 2,15,16,34,43 There is no available information that provides absolute parameters for safe stretching for patients after mastectomy or breast reconstruction. However, there are studies that have investigated the healing of traumatically injured muscles in athletes and have suggested that a period of relative immobilization for a couple of days might be beneficial, while longer periods of immobilization might lead to fibrosis rather than repair.…”
Section: Supplemental Video Onlinementioning
confidence: 99%
“…The technique is versatile and can also be used for other procedures such as conservative aspiration of a large scrotal hydrocoele. 1 High success rates have resulted in the technique of anastomosis remaining largely unchanged since this time. Here we describe a refinement on this technique that optimises venous length and helps prevent kinking of the draining AV fistula vein.…”
Section: Figure 2 Assembled Equipment For Seroma Drainagementioning
confidence: 99%